Nano collagenous fiber iron supplementing product and preparation method thereof
By using nanocollagen fibers combined with iron salt in food, the problem of low iron bioavailability in traditional iron-fortified foods is solved, and the efficient delivery and antioxidant effect of iron is achieved.
Patent Information
- Application Number
- CN202411800095.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Traditional iron-fortified food methods lead to low bioavailability of iron supplements in the human body and may cause adverse sensory changes and side effects.
Nanocollagen fiber iron supplementation products are prepared by covalently combining collagen with polyphenols and self-assembly in phosphate solution to form nano-scale collagen fibers and combined with iron salts.
It improves the bioavailability of iron, delays the release of iron in the gastrointestinal tract, reduces the stimulation to the gastrointestinal tract, and has good antioxidant ability.
Smart Images

Figure CN119679164A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of food processing, and in particular relates to a nano collagen fiber iron supplement product and a preparation method thereof. Background Art
[0002] Iron is an essential trace element for the human body and plays an important role in maintaining normal physiological functions of the body. At the same time, iron is also an important cofactor of various enzymes and participates in life processes such as electron transfer, DNA, RNA and protein synthesis, cell respiration, proliferation and differentiation, and regulation of gene expression. In the nervous system, iron is involved in the synthesis of myelin and various neurotransmitters such as norepinephrine, serotonin, and dopamine. Iron is also a functional component of myoglobin and hemoglobin in the body and plays an important role in oxygen transport and energy generation. Iron deficiency can limit the synthesis of hemoglobin, leading to the production of hypochromic and microcytic red blood cells, which in turn affects the normal development of the body. In addition, iron deficiency can also cause neurotransmitter synthesis disorders, leading to delayed behavioral functions such as language, motor balance, etc. About 1.62 billion people worldwide (accounting for 24.8% of the world's population) suffer from anemia, and the main cause of anemia is iron deficiency. Fortifying iron in food is a sustainable and cost-effective strategy to control iron deficiency and iron deficiency anemia.
[0003] The traditional method of iron fortification is to add iron nutritional fortifiers such as ferrous sulfate, ferrous fumarate, ferric pyrophosphate and sodium ferric ethylenediaminetetraacetate to food. However, the addition of these iron supplements usually causes adverse sensory changes, reducing the acceptability and utilization of food. In addition, direct consumption of iron salts may have some side effects, such as causing vomiting or gastric mucosal damage, and may also affect the composition and function of intestinal microbiota. Studies have shown that ferrous sulfate can promote the growth of methanogens and lead to a decrease in Lactobacillus, an important symbiotic bacteria in infants.
[0004] In recent years, emerging iron delivery systems have attracted widespread attention. Compared with synthetic polymers, food-derived iron delivery carriers have attracted much attention due to their outstanding features such as biodegradability, biocompatibility, excellent functionality, high nutritional value, low toxicity, and easy acceptance. Amino acids, peptides, proteins, and polysaccharides can chelate or encapsulate iron, thereby improving the bioavailability and intestinal absorption of iron, reducing sensory problems, reducing the interaction between iron and other components, and preventing direct contact between iron and the gastrointestinal tract to reduce side effects. However, the complexes formed by amino acids, peptides, and polysaccharides with iron are easily dissociated in the stomach. Therefore, providing a new iron delivery system that reasonably delays iron release is a problem that technicians in this field urgently need to solve. Summary of the invention
[0005] Aiming at the problem that iron is not easily digested in the human body and thus has low bioavailability, the present invention discloses a nano-collagen fiber iron supplement product and a preparation method thereof.
[0006] The present invention provides a method for preparing a nano-collagen fiber iron supplement product, comprising the following steps: (1) dissolving collagen in an acetic acid solution, mixing, and obtaining a collagen solution; wherein the collagen has a complete triple helix structure; (2) dissolving polyphenol in water, and adding the obtained polyphenol solution to the above collagen solution to obtain a collagen-polyphenol solution; wherein the molecular weight of the polyphenol is less than 500; (3) adding laccase to the collagen-polyphenol solution and mixing to obtain a polyphenol-collagen conjugate; (4) dialyzing the polyphenol collagen conjugate in a phosphate solution to obtain a polyphenol collagen composite fiber dispersion; (5) Adding iron salt to the above polyphenol collagen composite fiber dispersion, mixing to obtain polyphenol collagen fiber iron complex, dialyzing in deionized water to obtain nano collagen fiber iron supplement product.
[0007] Furthermore, in step (1), the collagen is extracted from livestock by-products by an acid method or an enzyme method; Preferably, the animal by-products include at least one of cattle hides, sheep hides or pig hides.
[0008] Furthermore, in step (1), the concentration of the acetic acid solution is 0.05 mmol / L; In step (1), the concentration of the obtained collagen solution is 0.5-2 mg / mL.
[0009] Further, in step (2), the concentration of the polyphenol solution is 40-240 μmol / L; In step (2), the volume ratio of the polyphenol solution to the collagen solution is 1:1. Furthermore, in step (3), the enzyme activity of the laccase is 40 U / mL; In step (3), the amount of laccase added is 60 U / g collagen, calculated based on the dry weight of collagen.
[0010] Furthermore, in step (4), the phosphate solution is a 0.1 M Na-phosphate buffer containing 100 mM NaCl and a pH of 6.2. Furthermore, in step (4) and step (5), the dialysis is performed using a dialysis bag with a molecular weight cutoff of 8000-14000Da.
[0011] Furthermore, in step (5), the iron salt includes at least one of ferrous sulfate, ferrous chloride, ferric chloride, ferrous lactate, ferrous gluconate, ferrous fumarate, and ferrous succinate.
[0012] Furthermore, in step (5), iron salt is added to the polyphenol collagen composite fiber dispersion at a mass ratio of collagen to iron ion of 4-6:1.
[0013] The present invention also provides a nano-collagen fiber iron supplement product prepared by any of the above-mentioned preparation methods.
[0014] The present invention has the following advantages: The present invention utilizes laccase to catalyze the covalent bonding of polyphenols and collagen, self-assembles to form fibers under a phosphate solution, mixes iron salt with a polyphenol collagen composite fiber dispersion, and prepares a polyphenol collagen fiber iron complex. The preparation method adopted by the present invention is simple to operate, and the prepared polyphenol collagen fiber iron complex has a high iron loading and good antioxidant capacity, helps to reduce oxidative stress reactions, delays the release of iron in the gastrointestinal tract, and thus increases the bioavailability of iron in digestion. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0016] Figure 1 The fluorescence spectra of the gallic acid collagen composite fibers with different concentrations provided in Test Example 1 of the present invention; Figure 2 Fourier transform infrared spectra of gallic acid collagen composite fibers with different concentrations provided in Test Example 1 of the present invention; Figure 3 A secondary structure ratio diagram of gallic acid collagen composite fibers with different concentrations provided in Test Example 1 of the present invention; Figure 4 Scanning electron microscope images of different concentrations of gallic acid collagen composite fibers provided in Test Example 1 of the present invention (AF are respectively collagen, collagen fibers, and gallic acid collagen composite fibers with final concentrations of system polyphenols of 20, 40, 80, and 120 μM; A is at a magnification of 1000 times; BF is at a magnification of 10,000 times); Figure 5 A graph showing the iron binding capacity of gallic acid collagen composite fibers with different concentrations provided in Test Example 1 of the present invention (lowercase letters in the graph indicate significant correlation at the p<0.05 level); Figure 6 Transmission scanning electron micrographs of the collagen-iron complex, collagen fiber-iron complex (GA-0-Fib), gallic acid collagen fiber-iron complex (GA-20-Fib), and tannin collagen fiber-iron complex (T-20-Fib) provided in Test Example 1 of the present invention; Figure 7 This is a graph showing the iron ion release curves of gallic acid collagen fiber-iron complexes with different concentrations during in vitro digestion provided in Test Example 1 of the present invention. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.
[0018] Protein aggregates degrade slowly in the stomach due to their structural characteristics, which helps to delay the release of iron and is more suitable as an iron delivery carrier. Collagen, as an important component of metazoan connective tissue, has excellent structural characteristics and multiple modification properties. Compared with collagen degradation products such as gelatin and collagen peptides, collagen molecules with a complete triple helix structure can self-assemble into fibers under physiological conditions similar to those in vivo. This ordered structure can improve the thermal stability and resistance to enzymatic degradation of collagen, and can serve as an effective carrier for binding and delivering iron.
[0019] On the one hand, the embodiment of the present invention provides a method for preparing a nano-collagen fiber iron supplement product, comprising the following steps: (1) dissolving collagen in an acetic acid solution, mixing, and obtaining a collagen solution; wherein the collagen has a complete triple helix structure; (2) dissolving polyphenol in water, and adding the obtained polyphenol solution to the above collagen solution to obtain a collagen-polyphenol solution; wherein the molecular weight of the polyphenol is less than 500; (3) adding laccase to the collagen-polyphenol solution and mixing to obtain a polyphenol-collagen conjugate; (4) dialyzing the polyphenol collagen conjugate in a phosphate solution to obtain a polyphenol collagen composite fiber dispersion; (5) Adding iron salt to the above polyphenol collagen composite fiber dispersion, mixing to obtain polyphenol collagen fiber iron complex, dialyzing in deionized water to obtain nano collagen fiber iron supplement product. The preparation method of the nano collagen fiber iron supplement product proposed in the embodiment of the present invention adopts laccase to catalyze the covalent binding of collagen and low molecular weight polyphenols, and then assembles into polyphenol collagen composite fibers by non-covalent action in a phosphate solution. In this reaction, collagen is a soluble natural collagen with a complete triple helical structure, which has the characteristic of self-assembly to form fibers. Although it can self-assemble to form a fiber structure, due to its limited binding sites, the resulting fiber structure and iron binding force are not good. And the addition of low molecular weight polyphenols helps collagen to self-assemble to form fibers with uniform diameters, and this fiber morphology is more conducive to the combination of iron ions. The iron content of the obtained nano collagen fiber iron supplement product is high, has antioxidant capacity, helps to reduce oxidative stress, delays the release of iron ions in the gastrointestinal tract, and reduces the stimulation to the gastrointestinal tract, and has potential application value in strengthening iron absorption in functional foods.
[0020] In step (1) of the embodiment of the present invention, collagen with a complete triple helix structure is selected as the reaction raw material. There are two main forms of collagen commonly found in the prior art: one is the collagen fibers peeled off from cowhide, sheepskin, etc. after being fully swollen by soaking in hydrochloric acid, which are visible to the naked eye and insoluble fibers. It has good mechanical properties and is generally used as a film-forming material; the other is the soluble collagen extracted from animal skin tissue by acid or enzyme method, which has a complete triple helix structure, but is generally used for direct compounding with iron, and the effect is poor. The embodiment of the present invention uses soluble collagen with a complete triple helix structure, which can be dissolved in acetic acid solution, and utilizes its self-assembly to form fibers. Under the catalysis of laccase, this soluble collagen with a complete triple helix structure is covalently bonded to polyphenols, and then non-covalently self-assembled to form nano-scale collagen fibers with uniform diameters. This fiber state is more conducive to the binding of iron ions thereto.
[0021] In one embodiment of the present invention, in step (1), the collagen is extracted from livestock by-products by an acid method or an enzyme method. The livestock by-products include at least one of cowhide, sheepskin or pigskin. Among them, the acid method [ZHU Q, LI Y, LI S, et al. Fabrication and characterization of acid soluble collagenstabilized Pickering emulsions [J]. Food Hydrocolloids, 2020, 106, 105875] and the enzyme method [ZHU S, YUAN Q, YANG M, et al. A quantitative comparable study on multi-hierarchy conformation of acid and pepsin-solubilized collagens from the skin of grass carp (Ctenopharyngodon idella) [J]. Materials Science and Engineering: C, 2019, 96, 446-457] are both conventional methods. This type of collagen has the advantages of wide sources and low cost.
[0022] In one embodiment of the present invention, in step (1), mixing is performed by stirring.
[0023] In one embodiment of the present invention, in step (1), the concentration of the acetic acid solution is 0.05 mmol / L. The concentration of the obtained collagen solution is 0.5-2 mg / mL. It should be noted here that the collagen solutions are all acetic acid solutions of collagen.
[0024] In one embodiment of the present invention, in step (1), the stirring is specifically carried out in a water bath at 25° C. until completely dissolved. In step (2) of the embodiment of the present invention, low molecular weight polyphenols are selected to cross-link with collagen, which helps collagen to self-assemble into fibers with uniform diameter. This fiber morphology is more conducive to the binding of iron ions thereto. When the molecular weight of polyphenols is large, it will cause excessive aggregation of collagen, and iron ions will gather in clusters at the intersection of fibers, which is not conducive to the uniform attachment of iron ions.
[0025] In one embodiment of the present invention, in step (2), the polyphenols include at least one of gallic acid, ferulic acid, caffeic acid, epicatechin, and epigallocatechin gallate. The molecular weight of gallic acid is 171, the molecular weight of ferulic acid is 194.18, the molecular weight of caffeic acid is 180.16, the molecular weight of epicatechin is 290.27, and the molecular weight of epigallocatechin gallate is 458.38.
[0026] In one embodiment of the present invention, in step (2), the concentration of the polyphenol solution is 40-240 μmol / L.
[0027] In one embodiment of the present invention, in step (2), the volume ratio of the polyphenol solution to the collagen solution is 1:1. In step (3) of the embodiment of the present invention, the covalent bonding of collagen and polyphenols is achieved by continuous oscillation under the action of laccase.
[0028] In one embodiment of the present invention, in step (3), the enzyme activity of the laccase is 40 U / mL.
[0029] In one embodiment of the present invention, in step (3), the amount of laccase added is 60 U / g collagen, calculated based on the dry weight of collagen.
[0030] In one embodiment of the present invention, in step (3), mixing is performed by continuous oscillation. Preferably, in step (3), the continuous oscillation time is 4 h. More preferably, in step (3), oscillation is performed by a constant temperature oscillator, wherein the temperature of the constant temperature oscillator is 25 ° C and the speed of the constant temperature oscillator is 100 rpm.
[0031] In step (4) of the embodiment of the present invention, the polyphenol collagen conjugate is dialyzed in a phosphate solution and self-assembled through non-covalent interaction to form polyphenol collagen composite fibers.
[0032] In one embodiment of the present invention, in step (4), the phosphate solution is a 0.1 M Na-phosphate buffer containing 100 mM NaCl and a pH of 6.2. In one embodiment of the present invention, in step (4), the dialysis is performed using a dialysis bag with a molecular weight cutoff of 8000-14000Da. Preferably, in step (4), the dialysis time is 8-24 hours. More preferably, in step (4), the dialysis time is 12 hours.
[0033] In step (5) of the embodiment of the present invention, iron salt is added to the polyphenol collagen composite fiber dispersion to form a polyphenol collagen fiber iron complex under continuous oscillation, which is then dialyzed in deionized water to obtain a nano-collagen fiber iron supplement product.
[0034] In one embodiment of the present invention, in step (5), the iron salt includes at least one of ferrous sulfate, ferrous chloride, ferric chloride, ferrous lactate, ferrous gluconate, ferrous fumarate, and ferrous succinate.
[0035] In one embodiment of the present invention, in step (5), the iron salt is added to the polyphenol collagen composite fiber dispersion at a mass ratio of collagen to iron ions of 4-6:1. Preferably, in step (5), the iron salt is added to the polyphenol collagen composite fiber dispersion at a mass ratio of collagen to iron ions of 5:1. In one embodiment of the present invention, in step (5), the dialysis is performed using a dialysis bag with a molecular weight cutoff of 8000-14000Da. Preferably, in step (5), the dialysis time is 12-36 hours. More preferably, in step (5), the dialysis time is 24 hours.
[0036] In one embodiment of the present invention, in step (5), the nano-collagen fiber iron supplement product is retained in liquid form, or in powder form after freeze-drying. In one embodiment of the present invention, in step (5), mixing is performed by continuous oscillation. Preferably, in step (5), the continuous oscillation time is 2-6 h. Preferably, in step (3), the continuous oscillation time is 4 h. More preferably, in step (5), oscillation is performed by a constant temperature oscillator, wherein the temperature of the constant temperature oscillator is 25 ° C and the speed of the constant temperature oscillator is 100 rpm.
[0037] On the other hand, the embodiment of the present invention also proposes a nano-collagen fiber iron supplement product prepared by the above preparation method. The polyphenol collagen composite fiber prepared by the present invention has good iron binding properties. The addition of polyphenols can effectively increase the iron ion binding capacity of collagen fibers. The iron content of the prepared polyphenol collagen fiber iron complex is 5-7.5%, which is higher than the heme iron enhancer; in vitro digestion experiments have proved that the polyphenol collagen composite fiber can effectively delay the release of iron ions in the gastric phase; at the same time, the complex has good antioxidant capacity, which helps to reduce oxidative stress response.
[0038] The present invention will be described in detail below with reference to the embodiments and accompanying drawings.
[0039] Example 1 A method for preparing a nano-collagen fiber iron supplement product, comprising the following steps: (1) Dissolve 100 mg of natural acid-soluble collagen extracted by acid method in 100 mL of 0.05 mmol / L acetic acid solution, and stir the solution in a 25 °C water bath with a magnetic stirrer until it is completely dissolved; (2) Dissolve gallic acid in deionized water at a concentration of 40 μmol / L, add 100 mL of the solution to (1) at a volume ratio of 1:1 and stir evenly; (3) Using the laccase catalytic oxidation method, add laccase solution (0.15 mL, 40 U / mL) to (2) at a concentration of 60 U / g based on the dry weight of collagen, and oscillate the solution for 4 h using a constant temperature oscillator (25 °C, 100 rpm) to fully mix; (4) placing (3) into a 8000-14000Da dialysis bag and dialyzing for 12 h in 0.1 M Na-phosphate buffer containing 100 mM NaCl, pH 6.2 to form gallic acid-collagen composite fibers; (5) Add 100 mg⋅FeSO4⋅7H2O to (4) and stir until completely dissolved. Oscillate at room temperature for 4 h using a constant temperature oscillator (25 °C, 100 rpm); (6) Place (5) into a 8000-14000Da dialysis bag and dialyze in deionized water for 24 h to obtain a nano-collagen fiber iron supplement product.
[0040] Example 2 A method for preparing a nano-collagen fiber iron supplement product, comprising the following steps: (1) Dissolve 100 mg of natural acid-soluble collagen extracted by acid method in 100 mL of 0.05 mmol / L acetic acid solution, and stir the solution in a 25 °C water bath with a magnetic stirrer until it is completely dissolved; (2) Dissolve gallic acid in deionized water at a concentration of 80 μmol / L, add 100 mL of the solution to (1) at a volume ratio of 1:1 and stir evenly; (3) Using the laccase catalytic oxidation method, add laccase solution (0.15 mL, 40 U / mL) to (2) at a concentration of 60 U / g based on the dry weight of collagen, and oscillate the solution for 4 h using a constant temperature oscillator (25 °C, 100 rpm) to fully mix; (4) placing (3) into a 8000-14000Da dialysis bag and dialyzing for 12 h in 0.1 M Na-phosphate buffer containing 100 mM NaCl, pH 6.2 to form gallic acid-collagen composite fibers; (5) Add 100 mg⋅FeSO4⋅7H2O to (4) and stir until completely dissolved. Oscillate at room temperature for 4 h using a constant temperature oscillator (25 °C, 100 rpm); (6) Place (5) into a 8000-14000Da dialysis bag and dialyze in deionized water for 24 h to obtain a nano-collagen fiber iron supplement product.
[0041] Example 3 A method for preparing a nano-collagen fiber iron supplement product, comprising the following steps: (1) Dissolve 100 mg of natural acid-soluble collagen extracted by acid method in 100 mL of 0.05 M acetic acid solution, and stir the solution in a 25 °C water bath with a magnetic stirrer until it is completely dissolved; (2) Dissolve gallic acid in deionized water at a concentration of 160 μmol / L, add 100 mL of the solution to (1) at a volume ratio of 1:1 and stir evenly; (3) Using the laccase catalytic oxidation method, add laccase solution (0.15 mL, 40 U / mL) to (2) at a concentration of 60 U / g based on the dry weight of collagen, and oscillate the solution for 4 h using a constant temperature oscillator (25 °C, 100 rpm) to fully mix; (4) placing (3) into a 8000-14000Da dialysis bag and dialyzing for 12 h in 0.1 M Na-phosphate buffer containing 100 mM NaCl, pH 6.2 to form gallic acid-collagen composite fibers; (5) Add 100 mg⋅FeSO4⋅7H2O to (4) and stir until completely dissolved. Oscillate at room temperature for 4 h using a constant temperature oscillator (25 °C, 100 rpm); (6) Place (5) into a 8000-14000Da dialysis bag and dialyze in deionized water for 24 h to obtain a nano-collagen fiber iron supplement product.
[0042] Example 4 A method for preparing a nano-collagen fiber iron supplement product, comprising the following steps: (1) Dissolve 100 mg of natural acid-soluble collagen extracted by acid method in 100 mL of 0.05 mmol / L acetic acid solution, and stir the solution in a 25 °C water bath with a magnetic stirrer until it is completely dissolved; (2) Dissolve gallic acid in deionized water at a concentration of 240 μmol / L, add 100 mL of the solution to (1) at a volume ratio of 1:1 and stir evenly; (3) Using the laccase catalytic oxidation method, add laccase solution (0.15 mL, 40 U / mL) to (2) at a concentration of 60 U / g based on the dry weight of collagen, and oscillate the solution for 4 h using a constant temperature oscillator (25 °C, 100 rpm) to fully mix; (4) placing (3) into a 8000-14000Da dialysis bag and dialyzing for 12 h in 0.1 M Na-phosphate buffer containing 100 mM NaCl, pH 6.2 to form gallic acid-collagen composite fibers; (5) Add 100 mg⋅FeSO4⋅7H2O to (4) and stir until completely dissolved. Oscillate at room temperature for 4 h using a constant temperature oscillator (25 °C, 100 rpm); (6) Place (5) into a 8000-14000Da dialysis bag and dialyze in deionized water for 24 h to obtain a nano-collagen fiber iron supplement product.
[0043] Comparative Example 1 A method for preparing a collagen-iron complex (without adding polyphenols and without fiber formation) comprises the following steps: (1) Dissolve 100 mg of natural acid-soluble collagen extracted by acid method in 100 mL of 0.05 mmol / L acetic acid solution, and stir the solution in a 25 °C water bath with a magnetic stirrer until it is completely dissolved; (2) Add 100 mL of deionized water to (1) and stir evenly; (3) Add 100 mg⋅FeSO4⋅7H2O to (2) and stir until completely dissolved. Oscillate at room temperature for 4 h using a constant temperature oscillator (25 °C, 100 rpm). (4) Place (3) into a 8000-14000Da dialysis bag and dialyze in deionized water for 24 h to obtain a collagen iron complex.
[0044] Comparative Example 2 A method for preparing a collagen fiber-iron complex (without adding polyphenols), comprising the following steps: (1) Dissolve 100 mg of natural acid-soluble collagen extracted by acid method in 100 mL of 0.05 mmol / L acetic acid solution, and stir the solution in a 25 °C water bath with a magnetic stirrer until it is completely dissolved; (2) Add 100 mL of deionized water to (1) and stir evenly; (3) (2) was placed in a 8000-14000Da dialysis bag and dialyzed in 0.1 M Na-phosphate buffer containing 100 mM NaCl, pH 6.2 for 12 h to form collagen fibers; (4) Add 100 mg⋅FeSO4⋅7H2O to (3) and stir until completely dissolved. Oscillate at room temperature for 4 h using a constant temperature oscillator (25 °C, 100 rpm); (5) Place (4) into a 8000-14000Da dialysis bag and dialyze in deionized water for 24 h to obtain a collagen fiber-iron complex. Comparative Example 3 A method for preparing a nano-collagen fiber iron supplement product (adding high molecular weight polyphenols) Same as Example 1, except that tannin is used to replace gallic acid, and the molecular weight of tannin is 1701.01. Test Example 1 1. Intrinsic fluorescence analysis of polyphenol-collagen composite fibers The gallic acid collagen composite fibers (respectively denoted as GA-20-Fib, GA-40-Fib, GA-80-Fib, and GA-120-Fib) prepared in Examples 1-4, the collagen fibers (respectively denoted as GA-0-Fib) prepared in Comparative Example 2, and 1.0 mg of acid-soluble collagen were dissolved in 2 mL of deionized water, and the fluorescent groups in the protein molecules were scanned using a fluorescence spectrophotometer. The excitation wavelength was 280 nm, the emission wavelength was 290-440 nm, the voltage was fixed at 600 V, the slit width was 5 nm, and the scanning speed was fixed at 240 nm / min.
[0045] Attached Figure 1 The results showed that acid-soluble collagen had a maximum absorption peak at 313 nm and no absorption peak at 350 nm, which was consistent with the characteristic absorption peak of collagen. Collagen could initiate self-assembly to form collagen fibers in 0.1 M Na-phosphate buffer containing 100 mM NaCl and pH 6.2. After self-assembly, the intrinsic fluorescence intensity decreased, indicating that the exposed amino acids in the molecule itself participated in the fiber formation process. The addition of gallic acid reduced the fluorescence intensity of collagen fibers, and it gradually decreased with the increase of gallic acid concentration. This was due to the covalent interaction between the tyrosine residues of collagen and the quinone formed by laccase oxidation of gallic acid. This result showed that gallic acid was covalently linked to collagen after laccase catalyzed oxidation.
[0046] 2. Fourier Transform Infrared Spectroscopy (FTIR) Analysis of Polyphenol Collagen Composite Fibers Thermo Nicolet Avatar 370FTIR spectrometer (Vector 22, Bruker, Germany) with DTGS KBr detector (Thermo, Shanghai, China) was used to obtain the FTIR spectrum of gallic acid collagen composite fibers. First, 1 mg of gallic acid collagen composite fibers (respectively denoted as GA-20-Fib, GA-40-Fib, GA-80-Fib, and GA-120-Fib) prepared in Examples 1-4, collagen fibers (respectively denoted as GA-0-Fib) prepared in Comparative Example 2, and acid-soluble collagen were added to a mortar, and then 150 mg of potassium bromide (KBr) was added, the mixture was ground into powder and transferred into a mold for tableting. Each sample was subjected to a 4000 cm -1 Up to 500 cm -1 The scans were analyzed by OMNIC 8.2 software. The relative content of the secondary structure was obtained by performing baseline correction, smoothing, deconvolution and second-order derivative fitting on the amide bands and calculating the area of each subpeak.
[0047] Attached Figure 2 The results showed that the amide A band of acid-soluble collagen was at 3424.36 cm -1 The absorption peak at 2927.67 cm -1 The amide B band observed at 3404.89 cm-1 represents the asymmetric stretching of CH2. -1 The absorption peak of amide A band appears at , indicating that collagen forms hydrogen bonds during the assembly process. The addition of gallic acid has no obvious wavenumber shift on the infrared spectrum of collagen fibers. By performing Fourier self-deconvolution and Gaussian fitting on the amide I band, the proportions of β-folding, L-polyproline helix and β-turn of collagen, collagen fibers and collagen composite fibers with different concentrations of gallic acid were obtained. Figure 3 The results showed that the proportions of β-fold, L-polyproline helix and β-turn of collagen were 42%, 26% and 32%, respectively. After self-assembly of collagen, the proportion of L-polyproline helix decreased to 23%, and the proportion of β-turn increased. This indicates that the assembly of collagen is driven by hydrophobic interactions. When the concentration of gallic acid was 20-40 μmol / L, the proportion of β-turn of the composite fiber increased. With the increase of gallic acid concentration, it turned to β-fold. This indicates that the addition of gallic acid has a rearrangement effect on the secondary structure of the assembled collagen fibers.
[0048] 3. Scanning electron microscopy observation of the morphology of polyphenol collagen composite fibers Take a small amount of gallic acid collagen composite fibers (respectively denoted as GA-20-Fib, GA-40-Fib, GA-80-Fib, and GA-120-Fib) prepared in Examples 1-4, the collagen fibers (denoted as GA-0-Fib) prepared in Comparative Example 2, and acid-soluble collagen, respectively, and stick them on a sample stage with conductive glue. Then, all the samples are sprayed with gold for 3 min in an argon environment and scanned using a SEM (SU3800, Hitachi, Japan) at an acceleration voltage of 7.0 kV.
[0049] Attached Figure 4 The results showed that the freeze-dried collagen molecules showed a lamellar membrane structure connected by filaments. The thickness of the fibrils formed by the assembly of collagen at 25 ℃ and pH 6.2 was uneven, and the coarse fibrils were aggregated from the fine fibrils. With the increase of the amount of gallic acid added, the diameter of the gallic acid collagen composite fibers became larger and larger, and the diameter tended to be uniform, which showed that within the range of the addition amount, gallic acid promoted the self-assembly of collagen and could form nano-collagen fibers with a diameter of 70-90 nm.
[0050] 4. Analysis of iron binding capacity of polyphenol collagen composite fibers The iron-loaded gallic acid collagen composite fibers (respectively denoted as GA-20-Fib, GA-40-Fib, GA-80-Fib, and GA-120-Fib) obtained in Examples 1-4, the collagen fiber iron complex (represented as GA-0-Fib) obtained in Comparative Example 2, and the collagen iron complex of Comparative Example 1 were heated at 90 °C for 30 min, and the iron binding capacity of the samples was determined using phenanthroline. Take 0.5 mL of the test solution, add 0.1 mL of 10% ascorbic acid solution, and react for 1 h. Then add 0.4 mL of 10% ammonium acetate solution, add 0.1 mL of 12 mM phenanthroline solution, let stand at room temperature for 10 min, and read the absorbance at 562 nm with an enzyme reader. Replace the sample with water as a blank control. Use iron (II) standard solution (0-50 μM) as a standard curve.
[0051] Attached Figure 5The results show that the iron binding capacity of the collagen iron complex in comparative example 1 is 1.6%, and the iron binding capacity of the collagen fiber iron complex after self-assembly is increased to 5.0%. This shows that compared with collagen molecules, collagen fibers have a stronger affinity for iron ions. The addition of gallic acid increases the iron binding capacity of collagen fibers. When the gallic acid concentration is above 40 μmol / L, the iron binding capacity is significantly improved. When the system polyphenol concentration is 120 μmol / L, the iron binding capacity can reach 8.1%, which is three to four times the iron content of heme iron (1.0-2.5%). This shows that iron ions not only bind to collagen fibers, but also bind to gallic acid. The greater the amount of gallic acid added, the more iron ions bind to it, and the ortho-dihydroxy structure of gallic acid can form a coordination bond with iron ions.
[0052] 5. Transmission Electron Microscopy Analysis of Polyphenol-Collagen Fiber-Iron Complexes The dispersions of gallic acid collagen fiber iron complex (referred to as GA-20-Fib) with a polyphenol concentration of 20 μmol / L in Example 1, collagen iron complex in Comparative Example 1, and collagen fiber iron complex in Comparative Example 2 (referred to as GA-0-Fib) were scanned by transmission electron microscopy. 10 μL of the diluted sample was deposited on a carbon support film on a copper grid for 1 min, then rinsed with ultrapure water and dried. The iron distribution of the complex was analyzed by transmission electron microscopy at 100 kV, and EDS energy spectrum was used to analyze the iron element distribution of the complex.
[0053] Attached Figure 6 The results show that from left to right are Comparative Example 1 collagen iron complex, Comparative Example 2 collagen fiber iron complex, Example 1 gallic acid collagen fiber iron complex, and Comparative Example 3 tannin collagen fiber iron complex, respectively, from top to bottom, the structure diagram of the corresponding sample, the distribution diagram of iron elements in the sample displayed by dark field scanning energy spectrum analysis, and the combination diagram of the two. The collagen iron complex presents a small irregular rope-like structure, and iron ions can be seen attached to the collagen molecules under high-angle annular dark field scanning. The collagen fiber iron complex presents a fiber structure of varying thickness, and there is obvious iron ion aggregation on the collagen fiber with a larger diameter. The gallic acid collagen fiber iron complex presents a regular and orderly long fiber shape, and the iron ions are relatively evenly attached to the fiber. The tannin collagen fiber iron complex presents a fiber aggregation state, which is due to the fact that tannin is a highly polymerized compound in polyphenols, with a large molecular weight, which promotes excessive aggregation of collagen, and iron ions are gathered in clusters at the intersection of fibers, indicating that the addition of tannin is not conducive to the formation of a regular and orderly fiber structure of collagen, and is not conducive to the uniform attachment of iron ions. As mentioned in the review, the addition of gallic acid is beneficial for collagen to form an effective carrier that can load iron ions.
[0054] 6. In vitro digestion to detect iron ion release The dialysis diffusion method was used to analyze the release of iron ions in the gallic acid collagen fiber iron complexes prepared in Examples 1-4 (respectively denoted as GA-20-Fib, GA-40-Fib, GA-80-Fib, GA-120-Fib), the collagen fiber iron complex prepared in Comparative Example 2 (denoted as GA-0-Fib), and the collagen iron complex of Comparative Example 1 during simulated in vitro gastrointestinal digestion. Gastric and intestinal electrolytes were prepared according to Table 1. 2 mL of sample dispersion (5 mg / mL) was added to a dialysis bag (MWCO 8000-14000Da) and completely immersed in 50 mL of simulated gastric fluid (pH 2.0, 3.2 mg / mL pepsin dissolved in gastric electrolyte) for 2 h. The dialysis bag was then transferred to 50 mL of simulated intestinal fluid (pH 7.0, 10 mg / mL trypsin, 2.5 mg / mL bile salt dissolved in intestinal electrolyte) for 3 h. The dialysis was continuously shaken at 150 rpm at 37 °C. The dialysate was taken every 30 min, and the iron ion content in the dialysate was detected at 562 nm using the phenanthroline colorimetric method. The zero-order model fitting of the kinetic release curve of iron ions was performed using formula (1).
[0055] Q t = Q0+k0t (1) Where Q t is the amount of iron ions released in time t; Q0 is the initial amount of sample in the solution; k0 is the zero-order release constant.
[0056] Table 1. Configuration of electrolyte for in vitro digestion
[0057] Attached Figure 7The results showed that the iron ion release rate of collagen iron complex was 82% at 30 min of gastric digestion, and the iron ion release rate reached 93% at 2 h of gastric digestion. The iron ion release rate of collagen fiber iron complex was 74% at 30 min of gastric digestion, and the iron ion release rate was further increased with the extension of digestion time, reaching 84.5%. Compared with the first two, the gallic acid collagen fiber iron complex released iron ions at a relatively slow rate. The addition of polyphenols effectively reduced the iron ion release rate in the gastric phase, and it slowed down with the increase of polyphenol concentration. At 2 h of gastric digestion, the iron ion release rates of 20-120 μmol / L gallic acid collagen fiber iron complex were 58.2%, 40.3%, 36.9%, and 21.0%, respectively. This is because the gallic acid collagen composite fiber, as a protein aggregate, will slowly degrade in the stomach, which delays the release of iron, thereby retaining more iron ions into the intestine. Table 2 shows the iron ion release kinetics of different samples fitted by the zero-order model, and the apparent release constant k0 is calculated by the linear regression equation. In the rapid release phase, the release constant k0 of gallic acid collagen fiber iron complex was significantly lower than that of collagen protein iron complex and collagen fiber iron complex, which indicated that pepsin had a delayed effect on the hydrolysis of polyphenol collagen fiber iron complex.
[0058] In simulated intestinal fluid, the iron ion release rates of collagen iron complex, collagen fiber iron complex, and gallic acid collagen fiber iron complex were relatively stable. The release constant k0 of gallic acid collagen fiber iron complex increased, which was mainly due to the further hydrolysis of loose protein structure by trypsin in simulated intestinal fluid. The total iron ion release of collagen iron complex in simulated gastrointestinal digestion was 96.35%, the total iron ion release of collagen fiber iron complex was 92%, and the iron ion release rates of 20-120 μmol / L gallic acid collagen fiber iron complex were 68.98%, 50.25%, 48.37%, and 25.45%, respectively. Therefore, compared with collagen iron complex and collagen fiber iron complex, the tightly assembled gallic acid collagen fiber iron complex is conducive to delayed dissociation in an acidic environment, and its retention in the intestine is more conducive to the sustained release of iron ions.
[0059] Table 2 R of the zero-order model kinetic curve of iron ion release 2 and the release constant k0
[0060] 7. Analysis of the antioxidant capacity of polyphenol collagen fiber iron complex DPPH radical scavenging ability: Dissolve 2,2-diphenyl-1-picrylhydrazyl (DPPH, 1 mg) in 20 mL 95% ethanol to obtain DPPH working solution. Mix 2 mL DPPH working solution into 1 mL sample solution and react in the dark for 30 minutes. Measure the absorbance of the solution at 519 nm. Calculate the DPPH radical scavenging activity using formula (1): DPPH free radical scavenging rate (%) = (A0-A1) / A0×100 Formula (2) Where A0 is the absorbance of DPPH at 519 nm without adding sample, and A1 is the absorbance of DPPH at 519 nm with adding sample.
[0061] ABTS free radical scavenging ability: 10 mg of 2,2'-nitrogen-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) was dissolved in 2.6 mL of potassium persulfate solution to prepare ABTS stock solution, and the solution was reacted at room temperature in the dark for 16 h. The solution was diluted with deionized water to an absorbance of 0.70 at a wavelength of 734 nm. 1 mL of the sample solution was diluted to a certain concentration and 3 mL of ABTS solution was added. The mixture was shaken for 30 s and allowed to react at room temperature in the dark for 60 min and the absorbance at 734 nm was measured. The ABTS free radical scavenging activity was calculated using formula (3): ABST free radical scavenging rate (%) = (A0-A1) / A0×100 Formula (3) A0 and A1 represent the absorbance of ABTS at 734 nm without and with sample, respectively.
[0062] Table 3 shows the antioxidant capacity of the gallic acid collagen fiber iron complex. The results of DPPH free radical scavenging rate and ABTS free radical scavenging rate show that collagen iron complex, collagen fiber iron complex and gallic acid collagen fiber iron complex all have antioxidant capacity. As the concentration of gallic acid in the system increases, the antioxidant capacity of the gallic acid collagen fiber iron complex gradually increases, indicating that the prepared nano-collagen fiber iron supplement product helps to reduce oxidative stress response.
[0063] Table 3 Antioxidant capacity of collagen-iron complex, collagen fiber-iron complex and gallic acid collagen fiber-iron complex
[0064] Note: Different lowercase letters represent significant differences in horizontal direction (P<0.05).
[0065] From the comprehensive analysis of the above results 1-7, it is known that the nano-collagen fiber iron supplement product prepared by the present invention is characterized, and the endogenous fluorescence experiment shows that there is a covalent interaction between polyphenols and collagen; the infrared spectrum experiment shows that the addition of polyphenols will change the composition of the secondary structure of collagen fibers; the scanning electron microscope shows that the diameter of the prepared polyphenol collagen composite fiber increases and is more uniform, with a diameter of 70-90 nm; the iron binding capacity experiment shows that with the increase of polyphenol concentration, the iron binding amount of the composite fiber increases (5-8%); the transmission electron microscope shows that iron ions can be uniformly attached to the polyphenol collagen composite fiber; the in vitro digestion experiment shows that the addition of polyphenols effectively delays the release of iron ions in the gastric phase; the antioxidant capacity experiment shows that the polyphenol collagen fiber iron complex has good antioxidant capacity. Table 4 shows the content of each component of the nano-collagen fiber iron supplement product prepared by the present invention, with a collagen content of 89.3-94.5%, a polyphenol content of 0.5-3.2%, and an iron content of 5.0-7.5%. In summary, the polyphenol collagen fibers prepared in the present invention can be used as an effective carrier for delivering iron, and the polyphenol collagen fiber iron complex can effectively improve the bioavailability of iron in the human digestion process as a functional food.
[0066] Table 4 Content of each ingredient in nano-collagen fiber iron supplement products
[0067] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nano-collagen fiber iron supplement product, characterized in that: The steps include: (1) dissolving collagen in an acetic acid solution, mixing, and obtaining a collagen solution; wherein the collagen has a complete triple helix structure; (2) dissolving polyphenol in water, and adding the obtained polyphenol solution to the above collagen solution to obtain a collagen-polyphenol solution; wherein the molecular weight of the polyphenol is less than 500; (3) adding laccase to the collagen-polyphenol solution and mixing to obtain a polyphenol-collagen conjugate; (4) dialyzing the polyphenol collagen conjugate in a phosphate solution to obtain a polyphenol collagen composite fiber dispersion; (5) Adding iron salt to the above polyphenol collagen composite fiber dispersion, mixing to obtain polyphenol collagen fiber iron complex, dialyzing in deionized water to obtain nano collagen fiber iron supplement product.
2. The preparation method according to claim 1, characterized in that: In step (1), the collagen is extracted from livestock by-products by an acid method or an enzyme method; Preferably, the animal by-products include at least one of cattle hides, sheep hides or pig hides.
3. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the acetic acid solution is 0.05 mmol / L; In step (1), the concentration of the obtained collagen solution is 0.5-2 mg / mL.
4. The preparation method according to claim 3, characterized in that: In step (2), the concentration of the polyphenol solution is 40-240 μmol / L; In step (2), the volume ratio of the polyphenol solution to the collagen solution is 1:
1.
5. The preparation method according to claim 1, characterized in that: In step (3), the enzyme activity of the laccase is 40 U / mL; In step (3), the amount of laccase added is 60 U / g collagen, calculated based on the dry weight of collagen.
6. The preparation method according to claim 1, characterized in that: In step (4), the phosphate solution is a 0.1 M Na-phosphate buffer containing 100 mM NaCl and a pH of 6.
2.
7. The preparation method according to claim 1, characterized in that: In step (4) and step (5), the dialysis is performed using a dialysis bag with a molecular weight cutoff of 8000-14000Da.
8. The preparation method according to claim 1, characterized in that: In step (5), the iron salt includes at least one of ferrous sulfate, ferrous chloride, ferric chloride, ferrous lactate, ferrous gluconate, ferrous fumarate, and ferrous succinate.
9. The preparation method according to claim 1, characterized in that: In step (5), iron salt is added to the polyphenol collagen composite fiber dispersion at a mass ratio of collagen to iron ion of 4-6:
1.
10. The nano-collagen fiber iron supplement product prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Novel self-assembled collagen and preparation method thereof
CN107630058A
Method for preparing natural collagen / nano gold compound and synchronously monitoring natural collagen self-assembly
CN110426356A
Preparation method and application of pigskin collagen peptide-ferrous chelate
CN113980122A
Collagen fiber with high biocompatibility and high stability, and preparation method and application thereof
CN115747993A
Preparation method of collagen peptide-ferric pyrophosphate compound
CN116584660A